Pengaruh Media Pembelajaran Berupa Game Talking Stick terhadap Hasil Belajar dan Kemampuan Komunikasi Sains Peserta Didik pada Pembelajaran IPA - Suci Puspita Rini; Neng Sholihat (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study aims to assess the impact of using Talking Stick game as a learning media on students' learning outcomes and scientific communication skills in science lessons. This study was conducted using the Systematic Literature Review (SLR) method, by analyzing various relevant previous studies from elementary to secondary education levels. The research findings indicate that the Talking Stick learning technique can significantly improve student learning outcomes. This model has also been proven effective in improving science communication skills, conceptual understanding, active participation, and students' courage to express opinions during the learning process. The Talking Stick method emphasizes collaboration and involvement between students in a fun and interesting atmosphere. The use of various supporting media, such as question cards, posters, audio visuals, and student worksheets (LKS), increases the effectiveness of this method. The use of alternating sticks in question and answer sessions encourages students to be more confident and actively involved in the learning process. This also provides benefits for the development of students' critical thinking skills and emotional skills, which are very much in line with the needs of learning in the 21st century. The findings of this Talking Stick model research are recommended as an innovative strategy in science learning. Teachers are advised to combine it with interesting learning media to make the learning process more meaningful and enjoyable. tested the effectiveness of this method in various educational conditions. Furthermore, consistent application of the Talking Stick method can create an inclusive learning environment that is responsive to individual student needs. In the context of science learning, which often demands understanding of abstract concepts and problem-solving, this method can bridge the gap between theory and practice through active and reflective interaction.